A new bioactive isocoumarin from the mangrove-derived fungus Penicillium sp. TGM112. Issue 7 (3rd July 2022) - Zeng, Wei-Nv; Cai, Jin; Wang, Bin; Chen, Liang-Yu; Pan, Chen-Xin; Chen, Shi-Ji; Huang, Guo-Lei; Zheng, Cai-Juan
Abstract: A new isocoumarin, penicimarin N (1 ), along with five known compounds (2-6 ), were isolated from the mangrove-derived fungus Penicillium sp. TGM112. The structure of 1 was elucidated on the basis of extensive spectroscopic data analysis, and the absolute configuration of 1 was determined by comparison of their circular dichroism (CD) spectra with the literature. The structures of known compounds were determined by comparison with the literature data. All the isolated compounds were examined for their antioxidant and α -glucosidase activities. Compound 1 showed strong antioxidant activity with the IC50 value of 1.0 mM, and 1 also exhibited moderate inhibitory activity against α -glucosidase with the IC50 value of 620 μM. Abstract : UF0001